2017
DOI: 10.5388/aon.2017.17.4.213
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Hope, Self-care Agency and Quality of Life of Female Oncology Patients with Lymphedema

Abstract: 연구의 필요성림프부종은This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/3.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…In similar a studie, the self-care power of patients was found to be moderate (10). Unlike these study results, there are studies reporting high self-care power in cancer patients (20,21). We believe that this difference is caused by factors such as age, educational status, presence of chronic diseases, number of cycles and culture of patients in the sample group.…”
Section: Discussioncontrasting
confidence: 70%
“…In similar a studie, the self-care power of patients was found to be moderate (10). Unlike these study results, there are studies reporting high self-care power in cancer patients (20,21). We believe that this difference is caused by factors such as age, educational status, presence of chronic diseases, number of cycles and culture of patients in the sample group.…”
Section: Discussioncontrasting
confidence: 70%
“…The concept of self-care agency is one of the main concepts of the ” General Nursing Theory or Self-Care Failure Theory in Nursing ” and it is the combination of action and agency elements that determine an individual's self-care performance in maintaining and improving health. [ 41 ] Some studies reported that cancer patients had high self-care agency,[ 42 43 ] while others stated that they had moderate self-care agency. [ 44 45 46 ] In our study, the self-care agency of cancer patients with cachexia was significantly lower than cancer patients without cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…stated that self-care agency positively affected the quality of life in individuals with cancer. [ 42 ] In the literature, in studies conducted with patients with and without cancer, it is stated that self-care agency positively affects the quality of life. [ 48 49 50 ] Whether the self-care agency increases quality of life, or the increased quality of life affects the self-care agency positively should be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…However, a high self-care ability correlates to the proper management of various symptoms experienced by patients in the treatment process, leading to improved QoL [ 19 ]. In a study of female cancer patients, a higher self-care ability also correlated to a higher QoL [ 20 ], and in an international study, a higher self-care ability was found to lead to proper symptom management and improved QoL [ 21 ]. Self-care ability is a major factor that can help cancer patients return to normal life after receiving treatment, raise their functional independence, and improve their QoL.…”
Section: Introductionmentioning
confidence: 99%